2013
DOI: 10.2355/tetsutohagane.99.448
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Sinter Quality for Improvement in Gas Permeability of Blast Furnace

Abstract: 緒言 ・佐藤 道貴 2)Evaluation of Sinter Quality for Improvement in Gas Permeability of Blast Furnace Naoyuki Takeuchi, Yuji iwami, Takahide higuchi, Koichi Nushiro, Nobuyuki oyama and Michitaka saTo Synopsis : In the recent operation of blast furnace, it is supposed that high gas permeability of burden is important for low RAR and high PCR operation.In this work, sinter quality for improvement in gas permeability of blast furnace was investigated with reduction degradation and under-loadreduction tests. As the result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…In the case of addition of small amount of H2, the RDI value increased, whereas more increase in the H 2 concentration to 12% led to a decrease of RDI values. In contrast, Takeuchi et al 12) pointed out that influence of H 2 gas on reduction disintegration behavior is slightly difference from Murakami's conclusion. According to his report, the RDI value increased due to the increase in the H 2 concentration, but the influence of the H 2 concentration on the RDI valuye decreases in the range of the H 2 concentration of 3.8 to 6.8 vol%.…”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation
“…In the case of addition of small amount of H2, the RDI value increased, whereas more increase in the H 2 concentration to 12% led to a decrease of RDI values. In contrast, Takeuchi et al 12) pointed out that influence of H 2 gas on reduction disintegration behavior is slightly difference from Murakami's conclusion. According to his report, the RDI value increased due to the increase in the H 2 concentration, but the influence of the H 2 concentration on the RDI valuye decreases in the range of the H 2 concentration of 3.8 to 6.8 vol%.…”
Section: Introductionmentioning
confidence: 77%
“…[4][5][6][7][8][9][10][11][12][13] Although large numbers of studies of reduction disintegration of sinter with CO reduction were reported, [14][15][16][17] there is a few reports about reduction disintegration behavior associated with the H 2 reduction. 12,[18][19][20] The second problem is a decrease of Fe contents and an increase of SiO 2 contents of iron ore. [20][21][22] This causes increase of slag volume of sinter, resulting in increasing in the reducing agent ratio of the BF. 23) In contrast, Fe contents of pellet is higher as compared with the fine ore and stable, since their raw material is iron ore concentrates produced by a beneficiation process at the mining site.…”
Section: Introductionmentioning
confidence: 99%
“…The permeability of the cohesive zone was reduced at low-cokerate operation of the traditional blast furnace, which resulted in the production efficiency of the blast furnace being reduced. Many research studies have proved that thinness and low location of the cohesive zone can improve permeability which promoted low-coke-rate operation of the blast furnace [1][2][3][4]. Therefore, low position and thin cohesive zone are desirable characteristics in a blast furnace.…”
Section: Introductionmentioning
confidence: 99%